2008
DOI: 10.1111/j.1365-2761.2008.00922.x
|View full text |Cite
|
Sign up to set email alerts
|

Activity of the antimicrobial polypeptide piscidin 2 against fish ectoparasites

Abstract: The antiparasitic effects of piscidin 2, an antimicrobial polypeptide (AMPP) first isolated from mast cells of hybrid striped bass, were tested against three protistan ectoparasites of marine fish (the ciliates Cryptocaryon irritans and Trichodina sp., and the dinoflagellate Amyloodinium ocellatum) and one ciliate ectoparasite of freshwater fish (Ichthyophthirius multifiliis). I. multifiliis was the most susceptible parasite, with all theronts killed at 6.3 microg mL(-1) piscidin 2. The most resistant parasite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(63 citation statements)
references
References 36 publications
0
63
0
Order By: Relevance
“…According to Murray et al [51], mast cells could be directly involved in the destruction of pathogens and they provide further evidence for their multifunctional role in teleosts. Investigations have shown that mast cells of fish intestine and gills are involved in the production of specific AMPs, namely pleurocidin [51] and piscidins [21,23,30,33,61]. Piscidins have potent, broadspectrum antifungal and antibacterial activity and recently been found to have strong antiparasitic activity and were reported in gills of fish infected with three protistan ectoparasites [21], gills parasitized with a copepod [16], and gills infected with a monogenean [27].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…According to Murray et al [51], mast cells could be directly involved in the destruction of pathogens and they provide further evidence for their multifunctional role in teleosts. Investigations have shown that mast cells of fish intestine and gills are involved in the production of specific AMPs, namely pleurocidin [51] and piscidins [21,23,30,33,61]. Piscidins have potent, broadspectrum antifungal and antibacterial activity and recently been found to have strong antiparasitic activity and were reported in gills of fish infected with three protistan ectoparasites [21], gills parasitized with a copepod [16], and gills infected with a monogenean [27].…”
Section: Discussionmentioning
confidence: 98%
“…Piscidins are the prototypical AMP present in piscine MCs [16,21e23,27,29e31]. Piscidins have potent, broad-spectrum antibacterial and antifungal activity and have strong antiparasitic activity [16,21,27]. With regard to their mechanism of action, piscidins are thought to inhibit the synthesis of the cell wall, nucleic acids, and proteins or even inhibit enzymatic activity [32].…”
Section: Introductionmentioning
confidence: 99%
“…Various protective measures such as chemical, physical, and immunological methods have been developed to cure the disease caused by C. irritans [2][3][4][5]. Although these methods appear to be useful in a closed system such as an aquarium, in an open system such as the natural environment they are difficult to apply and/or are not very efficient.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, our results suggest that the potential involvement of innate immunity in the immobilization activities should also be considered, even when the serum was heat-inactivated. Colorni et al (2008) reported that piscidin three, an antimicrobial polypeptide, isolated from mast cells of hybrid striped bass was involved in immobilization responses and lethal to C. irritans theronts. It is not yet clear if other humoral factors such as complement, antimicrobial polypeptides, lysozyme, and lectins were boosted after the secondary exposure and resulted in higher immobilization titre compared to those post primary exposure.…”
Section: Discussionmentioning
confidence: 99%